Results of conservative, surgical treatment and rehabilitation of entrapment neuropathies in elderly patients in geriatric practice - Główczewska, Jadwiga; Nowacka, Krystyna; Główczewska-Siedlecka, Emilia; Mądra-Gackowska, Katarzyna; Siedlecki, Zygmunt; Szostak, Mateusz; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2017)
Entrapment neuropahies of upper limbs can cause mainly nocturnal neuropathic pain and impaired manual dexterity. The most common entrapment neuropathy is carpal tunnel syndrome and ulnar groove syndrome - ulnar nerve entrapment at the elbow. Treatment of entrapment neuropathies is both analgetic therapy and physiotherapy. In the cases of conservative treatment inefficiencies surgical decompression of nerves is performed. Authors of this oublication present results of both conservative and surgical of entrapment neuropathies in patients over 65 years old. Among the 17 patients with entraoment neuropathies 12 of them underwent surgical treatment. Achieved partial improvement in pain, mostly nocturnal and improving the quality of life and dexterity. In comparison, however, a group of younger patients who underwent surgery for the improvement was less spectacular, which may testify advancement and irreversibility of changes in older patients.